CONTENT OF CESIUM -137 IN FOOD PRODUCTS AND DRINKING WATER OF THE KASHKADARYA REGION OF THE REPUBLIC OF UZBEKISTAN - Yuldasheva F. U.; Mirsagatova M. R.; Kobiljonova Sh. R.; Niyazova O. A.; Imamova A. O.; Ergashov B. O. (Modern American Journals, 2026)
Radioactive substances can enter the body through the respiratory system, the gastrointestinal tract, contaminated water and food, as well as through damaged skin and even through intact skin. Cesium-137 is one of the most common artificial radionuclides, widely used in industry, medicine, and scientific research, which increases the likelihood of its release into the environment if radioactive sources are handled improperly. The relevance of this topic for the Kashkadarya region is due to the region's developed agricultural sector, extensive irrigated land, and the fact that a significant portion of the population obtains drinking water from underground and surface sources that undergo insufficient radiological monitoring. Despite this, data on the Cs-137 content in water and local agricultural products is limited, increasing the importance of assessing the radiation safety of food products.